Analyse de l’activité de joueurs dans deux jeux de rôle en ligne massivement multijoueurs - Floriane Owczarek (Activités)
Massively multiplayer online role-playing games offer a particular field for the study of narrative activity. This activity takes place within the universe of an online game where the players evolve and where they develop their character. What are the elements that can influence the emergence of this type of story? Can they be identified? To answer this question, we selected two distinct games: Rappelz (2006) and Landes Eternelles (2003); the former with commercial orientations, the latter managed by passionate volunteers. Using the NAM model, we conducted interviews with player-narrators, performed an analysis of forums and stories, and made observations within the two games themselves. We highlight the relationship between the stories written by players and the different respective or common elements found in the two games. Following the presentation of results, Landes Eternelles would seem to arouse far more narrative activity than Rappelz, where while such activity exists, it is less prolific. The difference can also be felt in the content, with different themes and different game elements being integrated into the story. At the end of the article will provide an opportunity to return to the method and its limits, and to support a new perspective of identity construction between the player and the game.